Role of the dorso and ventrolateral pons in cardiorespiratory hypothalamic defense responses. - Díaz-Casares, Amelia; López-González, Manuel Víctor; Dawid-Milner, Marc Stefan (InTechOpen, 2018)
Stimulation of discrete sites throughout the hypothalamus elicits autonomic and somatic responses. This chapter will stand out the cardiorespiratory changes evoked from stimulation of specific areas within the caudal hypothalamus: the perifornical area and the dorsomedial nucleus. The stimulation of these regions, known as the hypothalamic defense area (HDA), produces a pattern of visceral and somatic changes characteristic of the defense reaction, which includes tachypnea, tachycardia and a pressor response. A close review of the literature demonstrates that the changes observed during this defensive behavioral response are partially mediated by the interactions with pontine regions. These include the parabrachial complex, located in the dorsolateral pons, and the A5 region, located in the ventrolateral pons. Specific glutamatergic stimulation of cell bodies located within the parabrachial complex and A5 region evokes cardiorespiratory responses similar to those observed during stimulation of the HDA. This functional interaction suggests a possible role of glutamate pontine receptors in the modulation of the HDA response. This chapter describes the most important evidences confirming the implication of the dorso- and ventrolateral pons in the control of cardiorespiratory autonomic responses evoked from the perifornical and dorsomedial hypothalamus and the role of glutamate in this interaction.
Keywords: Hipotálamo; Health; Hypothalamic defense response; Dorsolateral pons; Ventrolateral pons; Hypothalamus; Deseases